The Resilience of Indonesiaâ€™s State Budget against Central Government Debt - Bintoro, Nugroho Suryo (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
The growth of central government debt in Indonesia is the subject of endless discussion for both economists and experts in other fields. Although the government uses this debt in order to increase Indonesia's competence through infrastructure development, there are problems in the form of previous accumulated debts. This accumulative debt is known as the concept of â€œdebt stockâ€ which is assessed through Indonesia's fiscal resilience (APBN) to measure the repayment capacity of new debts that will be made in the future. This ability will be seen using long-term data from 1990 to 2016 which is reflected in the variables of central government debt, government spending and revenue so that it is known that Indonesia's central government debt can still be said to be sustainable and the Indonesian government should prioritize productive expenditures in order to increase government revenues.